MATERNITY LEAVE POLICIES AND WAGE DISPARITY ON WOMEN WORKFORCE IN HARYANA - Ms. Priya Verma (Chelonian Research Foundation, 2024)
The state of Haryana has been grappling with the issue of low female workforce participation, with only 23.2% of women employed compared to 75.4% of men. Maternity leave policies and wage disparity are two significant factors that can impact women's decision to join and stay in the workforce. This study aims to explore the impact of maternity leave policies and wage disparity on women's workforce participation in Haryana. This study examines the interplay between maternity leave policies and wage disparity among women in Haryana's workforce. In scenarios where maternity leave is generous and accessible, women tend to experience improved job retention and career progression, mitigating wage gaps. Conversely, in environments with limited or inflexible leave, women face increased job insecurity and stagnation in earnings. A mixed-methods approach was adopted, combining both quantitative and qualitative data collection and analysis methods. A survey was conducted among 200 women employees in various sectors in Haryana, while 30 in-depth interviews were conducted with women who had taken maternity leave and returned to work. The results show that the current maternity leave policy of 26 weeks is inadequate, as many women reported having to take unpaid leave or compromise on their job roles during this period. Wage disparity was found to be a significant deterrent, with women earning an average of 22% less than their male counterparts. The study highlights the need for a more comprehensive and supportive maternity leave policy, as well as measures to address wage disparity. Recommendations include increasing the duration of maternity leave, introducing flexible work arrangements, and implementing policies to address wage disparity. The findings of this study have important implications for policymakers and employers in Haryana, highlighting the need for a more inclusive and supportive work environment that enables women to thrive in their careers.